The effect of PGPR and nityrogen application rates on the growth of rice (Oryza sativa) MR 219 - Maslan Malik, Muhammad Hafiz (2013)
Oryza sativa L. is the common species of rice planted in Asia. It is an important food crop in the world and forms the staple diet in Malaysians. To meet the challenge of feeding the world’s growing population more rice must be produced from less land with minimum cost and under environmentally adverse inputs. Overuse of chemical fertilizers will increase production costs and also environmental pollution. Therefore, plant growth promoting rhizobacteria (PGPR) are frequently used to improve rice yield production. It can increase nutrient uptake and can become an alternative source of elemental nitrogen for crop production. An experiment was conducted in laboratory and glasshouse condition with the following objectives: i) to determine the effect of PGPR on the growth of rice, ii) to determine the best rate of nitrogen application on the growth of rice, iii) to determine the interaction of inoculating bacteria and nitrogen fertilizer on the growth of MR219 rice variety. There were 6 treatments [T1 (0% N + UPMB10); T2 (25% N + UPMB10); T3 (50% N + UPMB10); T4 (100% N + UPMB10); T5 (0% N – UPMB10); T6 (100% N – UPMB10). This experiment was arranged in a Randomized Complete Block Design (RCBD). Plants were sampled at 70 days of growth. Parameters that were collected at day 70 during harvesting period were plant height, chlorophyll content, plant dry weight, NPK content in leaves tissue, root length, root surface area and root volume. Result shows that plant that inoculated with UPMB10 gives the highest result better than the plant that were not inoculated with UPMB10. The parameter that show significant difference is nitrogen content in leaves tissue. As a conclusion from the study, plant inoculated with UPMB10 can increase the plant growth.